A study of the possible effects of scheduling damages - Mus, Jakub (2016)
The present thesis investigates the possible effects of limiting the compensations victims can obtain in medical malpractice cases through schedules of noneconomic damages. While economic damages are rather simple to calculate, problems arise with respect to the assessment of noneconomic damages. To reduce both the variability in the compensations granted to victims and the perception of a high level of arbitrariness in determining noneconomic losses, many countries have adopted different types of ceilings to limit the nonmonetary component of malpractice compensations. While flat and tiered caps have been widely studied in the related literature, the effects of schedules are still debated due to the scarce available evidence. Using Italy as a case study, I investigated the likely impact of schedules on noneconomic damages on a number of key outcomes showing that this policy can affect patients´ behavior and the filing of malpractice claims. Schedules are associated to a lower number of claims as well as of claims not decided on the merit. These results seem to be due to a drop in the number of frivolous claims. In addition, under schedules, average compensation and trial duration results to be higher. This is consistent with the expectation that under schedules there is a higher frequency of claims involving serious injuries. Hence, results could be further explored and used also in Czech Republic policy.